Model Water Transfer Mechanisms as a Drought Preparation System. (5th September 2017) - Pease, Mike; Snyder, Tricia
Abstract: This article evaluates the suitability of two supply‐side drought management tools, Emergency Water Banks and Strategic Water Reserves for multi‐year severe drought periods. The limited sample‐size related to the implementation of either makes direct comparison impossible, but through case studies some cursory evaluation as to their efficacy and their limitations is possible. These short‐term tools take different approaches to increase the amount of water available for reallocation during drought. While neither are stand‐alone solutions, and may not be suitable for continual use, both hold potential to provide short‐term relief during periods of severe shortage. Both however, carry drawbacks that can undermine their efficacy, or preclude adequate support for their implementation.